Scalia/Ginsburg: A (Gentle) Parody of Operatic Proportions - Wang, Derrick (The Columbia Journal of Law & the Arts, 2015)
An American comic opera in one act inspired by the opinions of U.S. Supreme Court Justices Ruth Bader Ginsburg and Antonin Scalia.